Actuality of improving the efficiency of innovation activity in Ukraine - Serdiuk, V. R. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Modern state of the use of objects of industrial property is investigated in innovative development of economy of the country. Negative factors resulting in "idling" of inventor work and brake introduction of innovations are educed, recommendations about their removal are presented in the paper.